2019
DOI: 10.3390/agriculture9010024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Land Use and Land Cover on Hydraulic and Physical Soil Properties at the Cerrado Agricultural Frontier

Abstract: Western Bahia is one of the most active agricultural frontiers in the world, which raises concern about its natural resources conservation, especially regarding water availability. This study evaluated the influence of five different land uses and land covers on physical and hydraulic soil properties, and developed pedotransfer functions to derive regional hydraulic properties. Significant changes between physical and hydraulic soil properties under agricultural areas and under natural vegetation cover were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The amount of water available for consumptive use by irrigation is directly linked to the streamflow of rivers, which depends on precipitation rates, duration of the wet season, maintenance of natural vegetation cover, and recharge rates of the aquifer. Although the changes in land cover do not significantly affect soil water infiltration in Western Bahia [ 40 ], it has been demonstrated elsewhere in the Cerrado that such changes may affect the water cycle [ 72 ]. Further studies specific to this region are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of water available for consumptive use by irrigation is directly linked to the streamflow of rivers, which depends on precipitation rates, duration of the wet season, maintenance of natural vegetation cover, and recharge rates of the aquifer. Although the changes in land cover do not significantly affect soil water infiltration in Western Bahia [ 40 ], it has been demonstrated elsewhere in the Cerrado that such changes may affect the water cycle [ 72 ]. Further studies specific to this region are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The soils of Western Bahia have developed on the geological formation of the Urucuia Group (Upper Cretaceous), which is dominated by quartz sandstone cemented by siliceous materials. The soils are sandy (clay content below 40%, with sand fraction between 70% and 90%) [ 40 ], deep, well drained, acidic (with high aluminum and Fe-oxide content), and of low fertility [ 44 ]. According to the Brazilian Soil Classification System, the predominant soils classes are Latossolos and Neossolos ( Fig 1 ), which are strongly associated with the typical vegetation of the Cerrado [ 34 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in agriculture, the hydraulic conductivity was found to be 4.9 cm/h, 4.0 cm/h and 3.5 cm/h for 0-20, 20-40 and 40-60 depths respectively. For rangeland, the trends of The results from a study conducted by [39] on the influence of land use and land cover on hydraulic and physical soil properties at the Cerrado Agricultural Frontier showed that the hydraulic conductivity in forest was 14.47 cm/h while in irrigated croplands, rainfed croplands and pasture, the hydraulic conductivity was 3.01 cm/h, 6.22 cm/h and 5.01 cm/h, respectively. A study done within the River Njoro watershed in Kenya showed similar results, where hydraulic conductivity was higher in forest (104 cm/h) than in grassland (69 cm/h) and in agriculture land (77 cm/h) [40].…”
Section: Discussionmentioning
confidence: 99%
“…These equations were obtained via regression curves from data collected on 34 plot areas in the USA with a wide range of textures, slopes, land use and land cover. The areas from the WEPP model possess different geological and climatological conditions from the soils in the Brazilian Semiarid Region; this is why local studies should be carried out, since empirical equations frequently have strong local character (Ghorbani-Dashtaki et al, 2016;Dionizio and Costa, 2019).…”
Section: Soil Datamentioning
confidence: 99%